Cost effective remote monitoring for mini hybrid automation system - Amin, A. F. M.; Rahman, A. I. A.; Salim, S. N. S.; Aris, I. B.; Suliaman, M. S.; Mohamad, R. T.; Zulkefle, A. A. (Research India Publications, 2015)
The growth of the communication system has been progressing rapidly and it provides facility in data acquisition system which can be remotely monitored via internet which so called Internet of Thing (IoT). In this project, a mini hybrid automation system is built and aims to produce energy for home appliances distributor. Circuit of the solar charger adapters available in the market will be carried out and the controller is able to distribute energy to all applications in the home. Research and analysis on the charger, solar and electric generator available in the market need for modification of the circuit. This project also includes research in solar charger, generator and the means of modification of the circuit. A standby generator is a back-up electrical system that operates automatically. Within seconds of a utility outage an automatic transfer switch senses the power loss, commands the generator to start and then transfers the electrical load to the generator. The standby generator begins supplying power to the circuits. The system with cost-effective control system based on Arduino as a microcontroller and TP-Link MR3020 for wireless internet communication with open source OpenWrt embedded firmware and all the operations can be monitored through web interface.